Using ExistenceSDK to make a ship MMO - Benedikt Aron Sigurþórsson 1999-; Jónas Freyr Bjarnason 2000-; Sigmar Snær Sigurðsson 2000-; Úlfur Ingólfsson 1998- (2023)
Arctic Theory is working on a new SDK plugin for Unreal Engine 5 called ExistenceSDK, we want to find out how easy or difficult it is to use their SDK to make an MMO, even for relative beginners. We will be detailing our processes and how we compare to our initial estimates.